Pergerseran Dialek Mesolect ke Dialek Acrolect dalam Penggunaan Bahasa Indonesia Artis Ibu Kota Asal Makassar - Wulandari, Putri; Nensilianti, Nensilianti; Jahrir, Andi Sahtiani (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2026)
This research aims to describe the forms of dialectal shift and identify its contributing factors. Employing a qualitative descriptive approach, data were collected from social media content, podcasts, films, and television programs featuring Makassar artists such as Arief Brata, Denny Sumargo, Indah Permatasari, Eca Aura, Maizura, and Musdalifah. The analysis was conducted using Joshua A. Fishman’s domain theory of language use. The findings reveal three forms of shift: functional, domain, and identity shifts. The main driving factors include urbanization, globalization, and the professional demands of the entertainment industry. The study concludes that this dialect shift is both a sociolinguistic and sociocultural phenomenon, reflecting the marginalization of local dialects in modern public communication.